Striatal Cholinergic Interneurons Control Physical Nicotine Withdrawal via Muscarinic Receptor Signaling - Baeksun Kim; Han Ah Kim; Junsung Woo; Hyeon‐Jeong Lee; Tae Kyoo Kim; Hophil Min; C. Justin Lee; Heh‐In Im (Advanced Science)
Abstract Striatal cholinergic interneurons (ChIs) provide acetylcholine tone to the striatum and govern motor functions. Nicotine withdrawal elicits physical symptoms that dysregulate motor behavior. Here, the role of striatal ChIs in physical nicotine withdrawal is investigated. Mice under RNAi‐dependent genetic inhibition of striatal ChIs (ChIGI) by suppressing the sodium channel subunit NaV1.1, lessening action potential generation and activity‐dependent acetylcholine release is first generated. ChIGI markedly reduced the somatic signs of nicotine withdrawal without affecting other nicotine‐dependent or striatum‐associated behaviors. Multielectrode array (MEA) recording revealed that ChIGI reversed ex vivo nicotine‐induced alterations in the number of neural population spikes in the dorsal striatum. Notably, the drug repurposing strategy revealed that a clinically‐approved antimuscarinic drug, procyclidine, fully mimicked the therapeutic electrophysiological effects of ChIGI. Furthermore, both ChIGI and procyclidine prevented the nicotine withdrawal‐induced reduction in striatal dopamine release in vivo. Lastly, therapeutic intervention with procyclidine dose‐dependently diminished the physical signs of nicotine withdrawal. The data demonstrated that the striatal ChIs are a critical substrate of physical nicotine withdrawal and that muscarinic antagonism holds therapeutic potential against nicotine withdrawal.